Monitoring persistent organic chemicals in Antarctica in support of global chemical policy: a horizon scan of priority actions and challenges - Bengtson Nash, Susan; Bohlin-Nizzetto, Pernilla; Galban-Malagon, Cristobal; Corsolini, Simonetta; Cincinelli, Alessandra; Lohmann, Rainer (The Lancet Planetary Health, 2023)
Summary Global production and emission of chemicals exceeds societal capacities for assessment and monitoring. This situation calls for improved chemical regulatory policy frameworks and increased support for expedited decision making within existing frameworks. The polar regions of the Earth represent unique sentinel areas for the study of global chemical behaviour, and data arising from these areas can strengthen existing policy frameworks. However, chemical pollution research and monitoring in the Antarctic is underdeveloped, with geopolitical complexities and the absence of legal recognition of international chemical policy serving to neutralise progress made in other global regions. This Personal View represents a horizon scan by the action group Input Pathways of Persistent Organic Pollutants to Antarctica, of the Scientific Committee for Antarctic Research. Four priority research and research facilitation gaps are outlined, with recommendations for Antarctica Treaty parties for strategic action against these priorities.
Keywords: Antarktis; Sørishavet; forskning; forvaltning; helse; miljøgifter

Communicating the best available science to inform Antarctic policy and management: a practical introduction for researchers - Hughes, Kevin A.; Lowther, Andrew; Gilbert, Neil; Waluda, Claire M.; Lee, Jasmine R. (Antarctic Science, 2023)
Communication at the science-policy interface can be bewildering not only for early-career researchers, but also for many within the research community. In the context of Antarctica and the Southern Ocean, decision-makers operating within the Antarctic Treaty System (ATS) aspire to use the best available science as a basis for their decision-making. Therefore, to maximize the impact of Antarctic Treaty Parties' substantial investment in southern polar research, researchers wishing to contribute to policy and management must understand 1) how their work relates to and can potentially inform Antarctic and/or global policy and 2) the available mechanisms by which their research can be communicated to decision-makers. Recognizing these needs, we describe the main legal instruments relevant to Antarctic governance (primarily the ATS) and the associated meetings and stakeholders that contribute to policy development for the region. We highlight effective mechanisms by which Antarctic researchers may communicate their science into the policy realm, including through National Delegations or the Scientific Committee on Antarctic Research (SCAR), and we detail the key contemporary topics of interest to decision-makers, including those issues where further research is needed. Finally, we describe challenges at the Antarctic science-policy interface that may potentially slow or halt policy development.
Edition: 2023/10/18 Publisher: Cambridge University Press
Keywords: Antarktis; Antarktistraktaten; Sørishavet; forskning; forvaltning; kommunikasjon

Moving mountains - when rocks and fluids interact - Engvik, Ane K.; Elvevold, Synnøve; Myhre, Per Inge; Sunde, Øyvind; Austrheim, Håkon (Fram forum, 2021)
Keywords: Dronning Maud Land; fjellene; forskning; geologi; mineralogi; nunataker

Networks of international co-authorship in journal articles about Antarctic research, 1998–2015 - Jang, Duckhee; Doh, Soogwan; Choi, Yongjin (Polar Research, 2020)
This study seeks insight into the social structure of Antarctic research from 1998 to 2015 by examining peer-reviewed journal articles listed in the Science Citation Index of the Web of Science database. This study identifies leading countries in peer-reviewed journal article output and applies social network analysis methods to identify countries where authors are collaborating with those affiliated with organizations in different countries. The results show that the number of publications on Antarctica and the proportion of international research collaboration increased from 23.0 to 33.2% during the period of time being considered. The number of articles published by authors affiliated with institutions in emerging countries such as China, Turkey, Brazil and South Korea rose, whereas the proportion of articles published by authors affiliated with institutions in the United States decreased. The largest proportion of academic publications pertaining to Antarctic research was within the natural sciences. Within this broad field, the majority of publications fell within Earth and related environmental sciences and the biological sciences. Social network analysis shows that Antarctic research moved towards a network, in which researchers are internationally more connected than ever before, with countries such as the United States, the United Kingdom, Germany, France and Australia in central positions. Sweden, Belgium and the Netherlands did not account for a high percentage of academic contributions but were still notable for their multinational collaborative research.
Keywords: Antarktis; forskning; publikasjoner; vitenskap

Antarctic minke whales find ice gaps along the ice edge in foraging grounds of the Indo-Pacific sector (60° E and 140° E) of the Southern Ocean - Konishi, Kenji; Isoda, Tatsuya; Bando, Takeharu; Minamikawa, Shingo; Kleivane, Lars (Polar Biology, 2020)
Keywords: Sørishavet; forskning; hvaler; krill; marin biologi; næring

Vannet som forandret fjellene - Engvik, Ane K (Bergtatt - Ane K. Engviks blogg, 2019)
Keywords: Dronning Maud Land; fjellene; forskning; geologi; mineralogi; nunataker

Wind Stress Mediated Variability of the Filchner Trough Overflow, Weddell Sea - Daae, Kjersti Birkeland; Darelius, Elin Maria K; Fer, Ilker; Østerhus, Svein; Ryan, Svenja (Journal of Geophysical Research: Oceans, 2018)
Keywords: Sørishavet; Weddellhavet; forskning; havstrømmer; oseanografi

Influence of meteorological parameters on atmospheric CO2 at Bharati, the Indian Antarctic research station - Pathakoti, Mahesh; Gaddamidi, Sreenivas; Gharai, Biswadip; Sudhakaran Syamala, Prijith; Venkata Narasimha Rao, Pamaraju; Choudhury, Saroj Bandh; Venkata Raghavendra, Kaila; Dadhwal, Vinay Kumar (Polar Research, 2018)
During the 35th Indian Scientific Expedition to Antarctica, measurements of atmospheric carbon dioxide (CO 2 ) were carried out using a Li-Cor CO 2 /H 2 O analyser at Bharati, the Indian Antarctic research station. This study examines the short-term variability of atmospheric CO 2 during the austral summer (January–February) of 2016. An average of 396.25 ± 4.20 ppm was observed during the study period. Meteorological parameters such as relative humidity, precipitation, wind speed, air temperature and atmospheric boundary layer height in conjunction with photosynthetically active radiation, the biological activity indicator which modulates atmospheric CO 2 concentration have been investigated. High wind speed (>20 m s −1 ) combined with precipitation scavenges CO 2 in the atmosphere, resulting in low concentrations at the study site. The lowest CO 2 concentration of 385 ppm coincided with heavy precipitation of 15 mm during study period. Statistical analysis of the data shows that precipitation and relative humidity independently correlated 55% (r = −0.55) and 32% (r = −0.32), respectively, with the variability of CO 2 mixing in the atmosphere at the study site. Atmospheric CO 2 was significantly correlated with precipitation alone with a p value of 0.003. Further, multiple regression analysis was performed to test the significant relation between variability of atmospheric CO 2 and meteorological parameters. Long-range air-mass transport analysis depicted that the majority of the air masses are reaching the study site through the oceanic region.
Keywords: Antarktis; atmosfæren; drivhuseffekt; drivhusgasser; forskning; karbondioksid; klimagasser; luftmassetransport; meteorologi; nedbør; polarområdene

On Roald Amundsen’s scientific achievements - Blix, Arnoldus Schytte (Polar Research, 2016)
This paper describes the significant direct and indirect contributions to science made by the Norwegian polar explorer Roald Amundsen in the period 1897–1924. It documents that his expeditions through the North-west Passage (1903–06) with Gjøa, to the South Pole (1910–12) with Fram and through the North-east Passage (1918–1920) and the Chukchi and East Siberian seas (1921–25) with Maud yielded vast amounts of published scientific material on meteorology, terrestrial magnetism, geology, palaeontology, oceanography, ethnography, zoology and botany, which, though celebrated at the time, have since received scant recognition in more recent assessments of Amundsen’s achievements. Keywords: Fridtjof Nansen; polar exploration; South Pole; North-west Passage; North-east Passage; H.U. Sverdrup.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; forskning; geologi; meteorologi; oseanografi

In memory of Torgny Vinje - a genuine polar scientist - Isaksson, Elisabeth; Gerland, Sebastian; Divine, Dmitry (Polar Research, 2016)
Keywords: Antarktis; Norsk Polarinstitutt; biografi; forskning; geofysikk; geologi; glasiologi; meteorologi; polarområdene

Delivering 21st century Antarctic and Southern Ocean science - Kennicutt, Mahlon C I I; Kim, Yeadong; Rogan-Finnemore, Michelle; Anandakrishnan, Sridhar; Chown, Steven L; Colwell, Steven (Antarctic Science, 2016)
The Antarctic Roadmap Challenges (ARC) project identified critical requirements to deliver high priority Antarctic research in the 21st century. The ARC project addressed the challenges of enabling technologies, facilitating access, providing logistics and infrastructure, and capitalizing on international co-operation. Technological requirements include: i) innovative automated in situ observing systems, sensors and interoperable platforms (including power demands), ii) realistic and holistic numerical models, iii) enhanced remote sensing and sensors, iv) expanded sample collection and retrieval technologies, and v) greater cyber-infrastructure to process ‘big data’ collection, transmission and analyses while promoting data accessibility. These technologies must be widely available, performance and reliability must be improved and technologies used elsewhere must be applied to the Antarctic. Considerable Antarctic research is field-based, making access to vital geographical targets essential. Future research will require continent- and ocean-wide environmentally responsible access to coastal and interior Antarctica and the Southern Ocean. Year-round access is indispensable. The cost of future Antarctic science is great but there are opportunities for all to participate commensurate with national resources, expertise and interests. The scope of future Antarctic research will necessitate enhanced and inventive interdisciplinary and international collaborations. The full promise of Antarctic science will only be realized if nations act together.
Keywords: Antarktis; forskning; vitenskap

A roadmap for Antarctic and Southern Ocean science for the next two decades and beyond - Kennicutt, M.C.; Chown, S.L.; Cassano, J.J.; Liggett, D.; Peck, L.S.; Massom, R.; Rintoul, S.R.; Storey, J.; Vaughan, D.G.; Wilson, T.J.; Allison, I.; Ayton, J.; et al. (Antarctic Science, 2015)
Antarctic and Southern Ocean science is vital to understanding natural variability, the processes that govern global change and the role of humans in the Earth and climate system. The potential for new knowledge to be gained from future Antarctic science is substantial. Therefore, the international Antarctic community came together to ‘scan the horizon’ to identify the highest priority scientific questions that researchers should aspire to answer in the next two decades and beyond. Wide consultation was a fundamental principle for the development of a collective, international view of the most important future directions in Antarctic science. From the many possibilities, the horizon scan identified 80 key scientific questions through structured debate, discussion, revision and voting. Questions were clustered into seven topics: i) Antarctic atmosphere and global connections, ii) Southern Ocean and sea ice in a warming world, iii) ice sheet and sea level, iv) the dynamic Earth, v) life on the precipice, vi) near-Earth space and beyond, and vii) human presence in Antarctica. Answering the questions identified by the horizon scan will require innovative experimental designs, novel applications of technology, invention of next-generation field and laboratory approaches, and expanded observing systems and networks. Unbiased, non-contaminating procedures will be required to retrieve the requisite air, biota, sediment, rock, ice and water samples. Sustained year-round access to Antarctica and the Southern Ocean will be essential to increase winter-time measurements. Improved models are needed that represent Antarctica and the Southern Ocean in the Earth System, and provide predictions at spatial and temporal resolutions useful for decision making. A co-ordinated portfolio of cross-disciplinary science, based on new models of international collaboration, will be essential as no scientist, programme or nation can realize these aspirations alone.
Edition: 2014/09/18 Publisher: Cambridge University Press
Keywords: Antarktis; Sørishavet; forskning; teknologi

Commercial fishing vessel as research vessels in the Antarctic – Requirements and solutions exemplified with a new vessel - Godø, Olav; Reiss, Christian; Siegel, V; Watkins, Jonathan (CCAMLR science journal of the Scientific Committee and the Commission for the Conservation of Antarctic Marine Living Resources, 2014)
Keywords: Antarktis; fiskefartøy; forskning; forskningsfartøy; klimaendringer; oseanografi; økosystem

Dietary overlap in inshore notothenioid fish from the Danco Coast, western Antarctic Peninsula - Casaux, Ricardo; Barrera-Oro, Esteban (Polar Research, 2013)
We carried out a dietary overlap analysis between notothenioid species by examining the stomach contents of more than 900 specimens collected in a fish assemblage at the Danco Coast, western Antarctic Peninsula, in the summer of 2000. Prey reoccurrences among fish species were 32.2%, with krill Euphausia superba, salps and the gammaridean Prostebeingia longicornis the most reoccurring prey. The diet similarity between species pairs was lower than 55%, in accordance with similar fish assemblages in the South Orkney Islands, the South Shetland Islands and the Antarctic Peninsula. Whereas at those localities the higher prey overlap was between krill-feeding fish species, at the Danco Coast it was between Trematomus bernacchii and Lepidonotothen nudifrons, Notothenia coriiceps and Notothenia rossii, Notothenia coriiceps and Parachaenichthyis charcoti, and Trematomus newnesi and Notothenia rossii, which shared primarily gammaridean amphipods, algae, fish and krill, respectively. Krill is normally the main prey of fish in summer in inshore waters of the western Antarctic Peninsula, but its density in January/February 2000 was notably lower than in previous years. Therefore, at the Danco Coast, under conditions of krill shortage, most of the notothenioid species foraged more intensively on alternative prey, such as gammarideans, fish and algae. The difference between areas in the pattern of dietary overlap might be related to differences in prey availability between years and to the degree of competition for targeted prey. Keywords: Fish dietary overlap; notothenioid fish; Antarctic Peninsula.
Keywords: Sørishavet; fisker; forskning; krill; marin biologi; plankton; økosystemer

Trends in Antarctic ecological research in Latin America shown by publications in international journals - Stotz, Gisela C; Salgado-Luarte, Cristian; Rios, Rodrigo S; Acuña-Rodriguez, Ian S; Carrasco-Urra, Fernando; Molina-Montenegro, Marco A; Gianoli, Ernesto (Polar Research, 2013)
Antarctica is a highly interesting region for ecologists because of its extreme climatic conditions and the uniqueness of its species. In this article, we describe the trends in Antarctic ecological research participation by Latin American countries. In a survey of articles indexed by the ISI Web of Science, we searched under the categories ‘‘Ecology,’’ ‘‘Biodiversity Conservation’’ and ‘‘Evolutionary Biology’’ and found a total of 254 research articles published by Latin American countries. We classified these articles according to the country of affiliation, kingdom of the study species, level of biological organization and environment. Our main finding is that there is a steady increase in the relative contribution of Latin American countries to Antarctic ecological research. Within each category, we found that marine studies are more common than terrestrial studies. Between the different kingdoms, most studies focus on animals and most studies use a community approach. The leading countries in terms of productivity were Argentina, Chile and Brazil, with Argentina showing the highest rate of increase. Keywords: Antarctica; Argentina; Brazil; Chile; research trends; scientific productivity.
Keywords: Antarktis; biodiversitet; forskning; vitenskap; økologi

Southern Weddell Sea shelf edge geomorphology: Implications for gully formation by the overflow of high-salinity water - Gales, Jennifer A; Larter, Robert David; Mitchell, Neil; Hillenbrand, Claus-Dieter; Østerhus, Svein; Shoosmith, Deb R (Journal of Geophysical Research: Earth Surface, 2012)
Keywords: Sørishavet; Weddellhavet; forskning; geomorfologi; isshelf; oseanografi

The intraseasonal variability of winter semester surface air temperature in Antarctica - Yu, Lejiang; Zhang, Zhanhai; Zhou, Mingyu; Zhong, Shiyuan; Sun, Bo; Hsu, Hsiaoming; Gao, Zhiqiu; Wu, Huiding; Ban, Junmei (Polar Research, 2011)
This study investigates systematically the intraseasonal variability of surface air temperature over Antarctica by applying empirical orthogonal function (EOF) analysis to the National Centers for Environmental Prediction, US Department of Energy, Reanalysis 2 data set for the period of 1979 through 2007. The results reveal the existence of two major intraseasonal oscillations of surface temperature with periods of 26 - 30 days and 14 days during the Antarctic winter season in the region south of 60°S. The first EOF mode shows a nearly uniform spatial pattern in Antarctica and the Southern Ocean associated with the Antarctic Oscillation. The mode-1 intraseasonal variability of the surface temperature leads that of upper atmosphere by one day with the largest correlation at 300-hPa level geopotential heights. The intraseasonal variability of the mode-1 EOF is closely related to the variations of surface net longwave radiation the total cloud cover over Antarctica. The other major EOF modes reveal the existence of eastward propagating phases over the Southern Ocean and marginal region in Antarctica. The leading two propagating modes respond to Pacific-South American modes. Meridional winds induced by the wave train from the tropics have a direct influence on the surface air temperature over the Southern Ocean and the marginal region of the Antarctic continent. Keywords: Antarctic climate, surface air temperature, intraseasonal variability, Antarctic Oscillation.
Keywords: Antarktis; forskning; klima; lufttemperatur

Review of Legacies and change in polar sciences: historical, legal and political reflections on the International Polar Year, edited by JM Shadian & M Tennberg - Dodds, Klaus (Polar Research, 2010)
The International Polar Year (IPY) of 2007–09 was an international scientific enterprise that encompassed all polar regions, and built on the legacies bequeathed by earlier endeavours stretching back to the late 19th century. The first such venture was initiated in 1882–83, the second was in 1932–33 and the last, the International Geophysical Year (IGY), occurred in 1957–58, and involved thousands of scientists working inter alia in the polar continent. Activity in the Arctic, for geopolitical reasons, was rather more limited, and was certainly not epitomized by free and unfettered scientific investigation. Sponsored by the International Council for Science, the most recent IPY was noteworthy for its explicit bi-polar focus, and its integration of the humanities and social sciences with the physical and environmental sciences. The role of indigenous communities was also notable in Arctic-based projects, a development that would have been inconceivable during the IGY. As with the IGY, however, a spectacular event in one of the theatres of scientific interest grabbed world headlines: in 1957 it was Sputnik orbiting the Earth, and in 2007 it was a Russian submersible planting a flag on the bottom of the central Arctic Ocean basin.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); bokanmeldelser; forskning; geopolitikk; internasjonal; polarområdene; samarbeid; vitenskap

Glaciomarine sediments and suspended particulate matter, Weddell Sea Shelf, Antarctica - Elverhøi, Anders; Roaldset, Elen (Polar Research, 2010)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; sedimentologi; stratigrafi

From the editor: halfway through the IPY—halfway for an Antarctic traverse - Goldman, Helle V (Polar Research, 2008)
April is here and we have just passed the midpoint of the International Polar Year (IPY), which began on 1 March 2007 and will conclude on 1 March 2009. The “year” stretches over 24 months to accommodate two summer field seasons in both polar regions. The northern summer is fast approaching, and scientists who will undertake a second IPY summer season in the Arctic are making their final preparations. At the opposite end of the planet, summer is over and scientists have wrapped up the first IPY field season. Those whose projects will carry on for a second summer season will have to wait until late this year to resume work in Antarctica.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norsk Polarinstitutt; ekspedisjoner; forskning; polarområdene; vitenskap

Hilsen fra Sørishavet - Pedersen, Ronald (Berlevågingen, 2008)
Keywords: Sørishavet; forskning; krill; marinbiologi; teknologi

National and institutional productivity and collaboration in Antarctic science: an analysis of 25 years of journal publications (1980–2004) - Dastidar, Prabir G. (Polar Research, 2007)
Journal publications on Antarctic science were analysed for a period of 25 years (1980–2004) through a set of scientometrics and network analysis techniques. The study is based on 10 942 records (research articles, review articles, letters, etc.) with the word fragment “antarc*” in the title published in 961 international, peer-reviewed journals and retrieved from Thomson Scientific’s Science Citation Index database. During the period under investigation, productivity increased threefold and there was a 13-fold increase in journal publications co-written by authors from different countries. The five nations with the highest output were the USA (with 26.7% of the total output), the UK (13.8%), Australia (9.7%), Germany (8.8%) and Italy (6.0%). The top five institutions in terms of journal publications were the British Antarctic Survey (972 publications), the Alfred Wegener Institute of Polar and Marine Research, Germany (475), the Australian Antarctic Division (312), the University of Tasmania, Australia (305), and the National Aeronautics and Space Administration, USA (293).
Keywords: Antarktis; dataanalyse; forskning; scientometri; tidsskriftspublikasjoner

Polar Research evolves, and Norway and the IPY - Goldman, Helle V (Polar Research, 2007)
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norge; Norsk Polarinstitutt; ekspedisjoner; forskning; polarområdene; vitenskap

Henrik Bull, the Antarctic Exploration Committee and the first confirmed landing on the Antarctic continent - McConville, Andrew (Polar Record, 2007)
Publisher: Cambridge University Press
Keywords: Antarktis; Carsten Egeberg Borchgrevink; D/S Antarctic; Henrik Johan Bull; Kapp Adare; Leonard Kristensen; Rosshavet; Victoria Land; ekspedisjoner; forskning; første landgang; oppdagelsesreiser

The Southern Ice Ocean Model Intercomparison Project (SIOMIP) - O'Farrell, Siobhan (Ice and climate news, 2007)
Keywords: Sørishavet; forskning; glasiologi; havis

Det første forskningstoktet til Antarktis - Tofte, Kari Østervold (Polaråret: et magasin om det internasjonale polaråret 2007-2008, 2007)
Keywords: Sørishavet; forskning; marin biologi

Antarctic sea ice processes and climate program, The International Polar Year - Ackley, Steve; Worby, Tony (Ice and climate news, 2006)
Keywords: Sørishavet; forskning; glasiologi; havis; klima

Perspectives on the Economic History of the Antarctic Region - Basberg, Bjørn L (Discussion paper Norges handelshøyskole, Institutt for samfunnsøkonomi, 2006)
Keywords: Antarktis; ekspedisjoner; fiskeindustri; forskning; hvalfangst; ressurser; turisme; økonomi; økonomisk historie

A hindcast simulation of Arctic and Antarctic sea ice variability, 1955-2001 - Fichefet, Thierry; Goosse, Hugues; Morales Maqueda, Miguel Angel (Polar Research, 2003)
A hindcast simulation of the Arctic and Antarctic sea ice variability during 1955–2001 has been performed with a global, coarse resolution ice–ocean model driven by the National Centers for Environmental Prediction / National Center for Atmospheric Research reanalysis daily surface air temperatures and winds. Both the mean state and variability of the ice packs over the satellite observing period are reasonably well reproduced by the model. Over the 47-year period, the simulated ice area (defined as the total ice-covered oceanic area) in each hemisphere experiences large decadal variability together with a decreasing trend of ~1 % per decade. In the Southern Hemisphere, this trend is mostly caused by an abrupt retreat of the ice cover during the second half of the 1970s and the beginning of the 1980s. The modelled ice volume also exhibits pronounced decadal variability, especially in the Northern Hemisphere. Besides these fluctuations, we detected a downward trend in Arctic ice volume of 1.8 % per decade and an upward trend in Antarctic ice volume of 1.5 % per decade. However, caution must be exercised when interpreting these trends because of the shortness of the simulation and the strong decadal variations. Furthermore, sensitivity experiments have revealed that the trend in Antarctic ice volume is model-dependent.
Keywords: Sørishavet; forskning; geofysikk; havis; observasjoner; polarområdene; satellitt; sjøis

Research on Antarctic affairs at the FNI (Nansen news, 2001)
Keywords: Antarktis; forskning

Norwegian use of the polar oceans as occupational arenas and exploration routes - Barr, Susan (Polar Record, 2001)
Publisher: Cambridge University Press
Keywords: Antarktis; Nordmenn; Norge; ekspedisjoner; forskning; geografi; historie; oppdagelsesreiser; polarområdene

IFIX - inductive data acquisition system: system for sub ice shelf data acquisition - Lothe, Torleif (Filchner-Ronne Ice Shelf Programme. Report, 2000)
Keywords: Antarktis; Sørishavet; forskning; teknologi

Belgica-ekspedisjonen : et hundreårsminne - Lie, Svein B (Norvegiana Nytt, 1997)
Keywords: Antarktis; Belgica ekspedisjon; forskning; oppdagelsesreiser; polarekspedisjoner

Antarktis - den siste villmark - Lorentsen, Svein-Håkon (NINA-Nytt, 1994)
Keywords: Dronning Maud Land; ekspedisjoner; forskning

Digestibility of krill (Euphausia superba and Thysanoessa sp.) in minke whales (Balaenoptera acutorostrata) and crabeater seals (Lobodon carcinophagus) - Mårtensson, Per-Erik; Nordøy, Erling S; Blix, Arnoldus Schytte (British Journal of Nutrition, 1994)
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; forskning; hvaler; krill; plankton; seler; zoologi

Resource limitation in a long-lived seabird, the Antarctic petrel Thalassoica antarctica: a twining experiment - Andersen, Reidar; Sæther, Bernt-Erik; Pedersen, Hans Christian (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1993)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

Aspects of the breeding biology of the Antarctic Petrel Thalassoica antarctica and the krill requirement of the chicks, at Svarthamaren in Mühlig-Hofmanfjella, Dronning Maud Land - Haftorn, Svein; Bech, Claus; Mehlum, Fridtjof (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1991)
Keywords: Dronning Maud Land; forskning; fugler; krill; ornitologi; zoologi

Notes on the south polar skua Catharacta Maccormicki breeding at Svarthamaren in Mühlig-Hofmannfjella, Dronning Maud Land - Haftorn, Svein; Bech, Claus; Mehlum, Fridtjof (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1991)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

The density of breeding and non-breeding Antarctic petrels at Svarthamaren, Dronning Maud Land, 1990 - Røv, Nils (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1991)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

Antarctic science in a historical perspective: changing roles and functional development - Indreeide, Thor Vidar (International Challenges, 1990)
Keywords: Antarktis; forskning; historie; vitenskap

SCAR in the ATS: conflict or harmony? - Rinaldi, Carlos (International Challenges, 1990)
Keywords: Antarktis; forskning; forvaltning; politikk

Resource management and the changing profile of science in Antarctica: a growing pressure for relevance? - Scully, Richard Tucker (International Challenges, 1990)
Keywords: Antarktis; forskning; forvaltning

Muscicolous Lepraria species and other leprarioid lichens in the Antarctic - Botnen, Astri; Øvstedal, Dag Olav (Polar Research, 1988)
Keywords: Dronning Maud Land; botanikk; forskning; lav; planter

Navigation to nest site in the snow petrel (Pagodroma nivea) - Haftorn, Svein; Mehlum, Fridtjof; Bech, Claus (The Condor, 1988)
Publisher: American Ornithological Society
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Size variation in the snow petrel Pagodroma nivea - Haftorn, Svein; Mehlum, Fridtjof; Bech, Claus (Notornis, 1988)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

Botany of Bouvetøya, South Atlantic Ocean. II. The terrestrial vegetation of Bouvetøya - Engelskjøn, Torstein (Polar Research, 1987)
Keywords: Bouvetøya; botanikk; forskning; planter

Breeding ecology of the Antarctic petrel Thalassoica Antarctica in Mühlig-Hofmannfjella, Dronning Maud Land - Fridtjof, Mehlum; Claus, Bech; Svein, Haftorn (Proceedings of the NIPR Symposium on Polar Biology, 1987)
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Interrelationships between egg dimensions, pore numbers, incubation time, and adult body mass in Procellariiformes with special reference to the Antarctic petrel Thalassoica antarctica - Mehlum, Fridtjof; Rahn, Hermann; Bech, Claus; Haftorn, Svein (Polar Research, 1987)
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Botany of two Antarctic mountain ranges: Gjelsvikfjella and Mühlig-Hofmannfjella, Dronning Maud Land. I. General ecology and development of the Antarctic cold desert cryptogam formation - Engelskjøn, Torstein (Polar Research, 1986)
Keywords: Dronning Maud Land; NARE 1984/85; botanikk; ekspedisjoner; forskning; planter

Antarktis petrellen - verdens mest hardføre fugl? - Haftorn, Svein (Viten : populær vitenskap, 1986)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

Fugler i de norske deler av Antarktis - Mehlum, Fridtjof (Vår fuglefauna, 1986)
Publisher: Norsk ornitologisk forening
Keywords: Bouvetøya; Dronning Maud Land; NARE 1984/85; Peter I. Øy; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Petreller i Dronning Maud Land - Mehlum, Fridtjof (Polarboken, 1986)
Publisher: Norsk Polarklubb
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

New records of terrestrial arthropods from Dronning Maud Land, Antarctica - Sømme, Lauritz (Polar Research, 1986)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; leddyr; zoologi

Terrestrial arthropods of Bouvetøya - Sømme, Lauritz (Polar Research, 1986)
Keywords: Bouvetøya; ekspedisjoner; forskning; midder; miter; virvelløse dyr

Suksess i syd: utvidet forskning i Antarktis (Forsvarets forum, 1985)
Keywords: Antarktis; Bouvetøya; Sørishavet; ekspedisjoner; forskning; logistikk

Automatic collection of tilt and strain data from tabular icebergs - Kristensen, Monica; Squire, Vernon A (Annals of Glaciology, 1983)
Publisher: Cambridge University Press
Keywords: Antarktis; forskning; glasiologi; isbreer

Insekter i Antarktis - Sømme, Lauritz (Forskningsnytt, 1983)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; insekter; zoologi

The Southern giant petrel Macronectes giganteus (Gmelin) on Bouvet Island - Haftorn, Svein; Voisin, Jean-Francois (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1982)
Keywords: Bouvetøya; forskning; fugler; ornitologi; zoologi

Present-day glaciation in the South Shetland Islands - Orheim, Olav; Govorukha, Leonid Sergeevich (Annals of Glaciology, 1982)
Publisher: Cambridge University Press
Keywords: Antarktis; firnsnø; forskning; glasiologi; isbreer; stratigrafi; vulkaner

Iceberg response to sea state - Orheim, Olav; Wadhams, Peter; Kristensen, Monica (Iceberg research, 1982)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; ekspedisjoner; forskning; isberg; isfjell; målinger

Basic volcanic rocks and tectonic setting. A discussion of the Zr-Ti-Y discrimination diagram and its suitability for classification purposes - Prestvik, Tore (Lithos, 1982)
Keywords: Bouvetøya; forskning; geologi; tektonikk; vulkaner

Supercooling and winter survival in terrestrial arthropods - Sømme, Lauritz (Comparative Biochemistry and Physiology Part A: Physiology, 1982)
Keywords: Antarktis; ekspedisjoner; forskning; kuldetoleranse; virvelløse dyr

Evidence for a late Wisconsin glaciation of the Weddell Sea - Elverhøi, Anders (Nature, 1981)
Keywords: Sørishavet; Weddellhavet; forskning; glasiologi; sedimentologi; stratigrafi

Morphology of the Weddell Sea and southwest Indian Ocean - Johnson, G Leonard; Vanney, Jean-René; Elverhøi, Anders; LaBrecque, John L (Deutsche Hydrografische Zeitschrift, 1981)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; havbunnen; tektonikk

Model for submarine glacial deposition - Orheim, Olav; Elverhøi, Anders (Annals of Glaciology, 1981)
Publisher: Cambridge University Press
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; havbunnen; oseanografi

Studies of icebergs, ice fronts and ice walls using side-scanning sonar - Klepsvik, John O; Fossum, Bjørn A (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; NARE 1978/79; ekspedisjoner; forskning; glasiologi; is; isberg; isfjell; isfront; morfologi; snø

Terrestrial arthropods from Vestfjella, Dronning Maud Land (Acari, Collembola), with notes on their taxonomy - Sømme, Lauritz (Insect Systematics & Evolution, 1980)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; leddyr; zoologi

Ice-shelf underwater morphology - Orheim, Olav (Journal of Glaciology, 1979)
Publisher: Cambridge University Press
Keywords: Antarktis; NARE 1976/77; ekspedisjoner; forskning; glasiologi; isshelf; morfologi

Plough marks in the Weddell Sea - Orheim, Olav (Journal of Glaciology, 1979)
Publisher: Cambridge University Press
Keywords: NARE 1976/77; Sørishavet; ekspedisjoner; forskning; havbunnen; oseanografi

Verdens kaldeste sjøvann - Foldvik, Arne; Gade, Herman G (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; observasjoner; oseanografi; sjøvann; vannmasser

Basaltene i Vestfjella og Gondwanalands historie - Furnes, Harald (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Dronning Maud Land; NARE 1976/77; ekspedisjoner; forskning; geokjemi; geologi; petrologi

Cryptopygus sverdrupi n.sp. A new species of Collembola (Isotomidae) from Sverdrupfjella, Antarctica, with notes on related species in five genera - Lawrence, Peter N (Norwegian Journal of Entomology, 1978)
Keywords: Dronning Maud Land; biologi; ekspedisjoner; forskning; leddyr

Hva den fossile magnetiseringen i Vestfjella kan fortelle - Løvlie, Reidar (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Dronning Maud Land; NARE 1976/77; ekspedisjoner; forskning; geologi; jordmagnetisme

Den norske Antarktis-ekspedisjonen 1976/77 - Orheim, Olav (Naturen, 1978)
Keywords: Antarktis; ekspedisjoner; forskning

Insektliv i Antarktis - Sømme, Lauritz (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; insekter; zoologi

Kuldetoleranse hos alpine og arktiske collemboler - Sømme, Lauritz (Entomologisk tidskrift, 1978)
Keywords: Antarktis; ekspedisjoner; entomologi; forskning; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Notes on the cold-hardiness of prostigmate mites from Vestfjella, Dronning Maud Land - Sømme, Lauritz (Norwegian Journal of Entomology, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; kuldetoleranse; midder; miter; virvelløse dyr; zoologi

The entomology of Antarctica, with special reference to Dronning Maud Land - Sømme, Lauritz (Norwegian Journal of Entomology, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; leddyr; zoologi

Hvor driver de antarktiske isfjellene? - Vinje, Torgny E (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; Weddellhavet; drivis; forskning; havis; havstrømmer; isberg; isdrift; issfjell; oseanografi; sjøis; sjøvann

The geology and petrology of Bouvetøya, south Atlantic Ocean - Imsland, Pall; Larsen, Jørgen Gutzon; Prestvik, Tore; Sigmond, Ellen M (Lithos, 1977)
Keywords: Bouvetøya; forskning; geologi; petrologi

Back to the Antarctic - Orheim, Olav (Research in Norway, 1977)
Publisher: Universitetsforl. Place: Oslo
Keywords: Bouvetøya; forskning; marinbiologi

Prostigmate mites (Acari, Prostigmata) from Sverdrupfjella, Dronning Maud Land, with description of four new species - Strandtmann, Russell W; Sømme, Lauritz (Norwegian Journal of Entomology, 1977)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; midder; miter; virvelløse dyr; zoologi

The biogeography of some marine planktonic diatoms - Hasle, Grethe Rytter (Deep Sea Research and Oceanographic Abstracts, 1976)
Keywords: Sørishavet; biogeografi; ekspedisjoner; forskning; fytoplankton; marinbiologi; plankton; planteplankton

A forgotten explorer: Carsten Egeberg Borchgrevink - Evans, Hugh B; Jones, A G E (Polar Record, 1974)
Publisher: Cambridge University Press
Keywords: Antarktis; biografi; ekspedisjoner; forskning; oppdagelsesreiser

The Antarctic Treaty consultative meetings : form and procedure - Hanevold, Truls (Cooperation and Conflict, 1971)
Keywords: Antarktis; Antarktistraktaten; forskning; internasjonal; politikk

Sydpolisen opptil 4000 m tykk: Sydpollandet har 95 pst. av isen i verden! - Lund, Thoralv (Polarposten, 1971)
Keywords: Antarktis; forskning

Tolv lands polarforskere til Antarktis-møte i Oslo - Lund, Thoralv (Polarposten, 1970)
Keywords: Antarktis; forskning

Norwegian pelagic sealing reconnaissance in the Scotia Sea, 1964 - Øritsland, Torger (Polar Record, 1970)
Publisher: Cambridge University Press
Keywords: Sørishavet; biologi; ekspedisjoner; forskning; marinbiologi; seler; zoologi

Amerikanske kvinnelige vitenskapsmenn studerer pingviner i Antarktis - Schroth, Charles (Polarposten, 1969)
Keywords: Antarktis; forskning

Antarktistraktaten, territorialkravene, forskningssamarbeidet - Bolin, Fredrik Th. (Polarboken, 1968)
Keywords: Antarktis; forskning; jus; politikk

Studies of surface snow at Plateau station - Lunde, Torbjørn (Antarctic Journal of the United States, 1968)
Keywords: Dronning Maud Land; ekspedisjoner; firnsnø; forskning; glasiologi; metamorfologi; morfologi; snø; stratigrafi

I telt på evig is: norsk polarekspedisjon til sydpollandet - Torkildsen, Torbjørn (Nå, 1968)
Keywords: Antarktis; Dronning Maud Land; ekspedisjoner; forskning; politikk

Samer i polarforskningen - Nissen, Kristian (Sameliv : Samisk selskaps årbok, 1963)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; ekspedisjonen; ekspedisjoner; forskning; første landgang; oppdagelsesreiser; overvintring; polarekspedisjoner; samer

Lys over "tåkeheimen" i sør: den videnskapelige serie fra Lars Christensens ekspedisjoner avlsuttet - Isachsen, Fridtjov (Norsk hvalfangst-tidende, 1962)
Keywords: Antarktis; Sørishavet; forskning; litteratur; naturvitenskap; vitenskap

The snow petrel Pagodroma nivea nesting in Dronning Maud Land - Løvenskiold, Herman L. (Ibis, 1960)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Norwegian air photography in Dronning Maud Land: Operation “Pingvin”, 1958–59 - Luncke, Bernhard (Polar Record, 1960)
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; ekspedisjoner; flyfoto; flyfotografering; forskning; luftfoto; topografi

Norsk Polarinstitutts målevirksomhet - Luncke, Bernhard (Norsk tidsskrift for jordskifte og landmåling, 1959)
Publisher: Norges jordskiftedommer- og landmålersamband Place: Oslo
Keywords: Antarktis; botanikk; ekspedisjoner; forskning; geodesi; geologi; glasiologi; kartlegging; meteorologi; ornitologi; oseanografi; zoologi

Air operations of the Norwegian-British-Swedish Antarctic Expedition in 1952 - Essen, Reinhold von (Polar Record, 1956)
Publisher: Cambridge University Press
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; flyfoto; forskning; geografi; luftfoto

The base of the Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Reece, Alan (Polar Record, 1953)
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

An International Expedition to Antarctica - Robin, Gordon de Quetteville (The Geographical Journal, 1953)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Robin, Gordon de Quetteville (Polar Record, 1953)
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Queen Maud Land Expedition - Robin, Gordon de Quetteville (Marine Observer, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

On Conditions for the Vernal Blooming of Phytoplankton - Sverdrup, Harald Ulrik (ICES Journal of Marine Science, 1953)
Keywords: Sørishavet; forskning; oseanografi; planteplankton

Physiological changes in blood in the Antarctic. A preliminary report - Wilson, Ove (British Medical Journal, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; forskning; fysiologi; medisin; observasjoner

A Radar Survey of the Ice Barrier - Higgins, Robert (Journal of Navigation, 1952)
Publisher: Cambridge University Press
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; geografi; geologi

Den norsk-brittisk-svenska antarktisexpeditionen 1949-52. Kort översikt av det andra årets arbeten - Liljequist, Gösta H; Schytt, Valter (Ymer, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Queen Maud Land. The Scientific Results of the International Expedition - Robin, Gordon de Quetteville (Geographical Magazine, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

The Norwegian-British-Swedish Antarctic Expedition (The Geographical Journal, 1951)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Life at Maudheim - Robin, Gordon de Quetteville (Geographical Magazine, 1951)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

An international expedition to Antarctica. The Voyage to Queen Maud Land - Roots, Ernest Frederick (Geographical Magazine, 1950)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; geologi

The Norwegian-Swedish-British Antarctic Expedition - Ahlmann, Hans Wilhelmsson (Tellus, 1949)
Publisher: Taylor & Francis
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

An international expedition to Antarctica - Kirwan, Laurence Patrick (Geographical Magazine, 1949)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Norwegian-British-Swedish expedition to the Antarctic (The Geographical Journal, 1948)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Den planerade norsk-svensk-brittiska Antarktis-expeditionen - Ahlmann, Hans Wilhelmsson (Ymer, 1948)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; geologi; glasiologi; meteorologi

"Brategg"-ekspedisjonen 1947-48 = The "Brategg" expedition 1947-48 (Norsk hvalfangst-tidende, 1947)
Keywords: Sørishavet; ekspedisjoner; forskning

Proposed British-Norwegian-Swedish Antarctic Expedition, 1948–50 (Polar Record, 1947)
Publisher: Cambridge University Press
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

The Falkland Islands Dependencies Survey, 1943-46 - Wordie, James Mann (Norsk hvalfangst-tidende, 1947)
Keywords: Antarktis; Sørishavet; ekspedisjoner; forskning; kartlegging; logistikk

Lars Christensen-ekspedisjonenes videnskapelige resultater - Holtedahl, Olaf (Polar-årboken, 1945)
Keywords: Antarktis; ekspedisjoner; forskning

Vår ishavsflåte og selfangsten : ishavsskutenes innsats i arktisk og antarktisk forskning - Hansen, Rolf (Vår Flåte, 1944)
Keywords: Sørishavet; ekspedisjoner; forskning; polarområdene; selfangst

Hvalrådets skrifter no.20: scientific results of marine biological reseqarch - Bergersen, Birger; Lie, J; Ruud, Johan T (Norsk hvalfangst-tidende, 1940)
Keywords: Sørishavet; forskning; hvaler; hvalfangst; marin zoologi

The Course of Antarctic Exploration between Longitudes 20° W. and 110° E. Notes on the map compiled to accompany the paper by Mr. Lars Christensen - Christensen, Lars (The Geographical Journal, 1939)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Lars Christensen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; oppdagelsesreiser

Ergebnisse der Norwegischen Antarktischen Expeditionen - Wüst, Georg (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1936)
Publisher: Perthes Place: Gotha
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; forskning; oppdagelsesreiser

Norwegians in the Antarctic - Aagaard, Bjarne (The American-Scandinavian Review, 1934)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Wie entsteht die Antarktische Konvergenz? - Sverdrup, Harald Ulrik (Annalen der Hydrographie und Maritimische Meteorologie, 1934)
Keywords: Sørishavet; forskning; havstrømmer; meteorologi; oseanografi

Walfang und Forschung in der Antarktis - Steinert, Hermann (Geographische Zeitschrift, 1933)
Keywords: Antarktis; Nordmenn; Norge; Norvegia ekspedisjonene; forskning; hvalfangst; pelagisk

On vertical circulation in the ocean due to the action of the wind with application to conditions within the Antarctic circumpolar current - Sverdrup, Harald Ulrik (Discovery Reports, 1933)
Keywords: Sørishavet; ekspedisjoner; forskning; havstrømmer; oseanografi

Polaraaret 1932-1933 (Norsk hvalfangst-tidende, 1932)
Keywords: Sørishavet; forskning; klima; meteorologi; oseanografi

Norwegian Explorations in the Antarctic, 1930-1931 - Isachsen, Gunnar (Geographical Review, 1932)
Publisher: [American Geographical Society, Wiley]
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjoner; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; meteorologi; oppdagelsesreiser; oseanografi

Antarctic Circumnavigation by the "Norvegia" (Geographical Review, 1931)
Publisher: [American Geographical Society, Wiley]
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjonen; ekspedisjoner; forskning; geografi; polarområdene

Antarctic Research by the Norvegia Expeditions and Others - Holtedahl, Olaf (The Geographical Journal, 1931)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Lars Christensen; Norvegia ekspedisjonene; Odd I.; Sørishavet; ekspedisjonen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

The "Norvegia" Antarctic Expedition of 1929-1930 - Riiser-Larsen, Hjalmar (Geographical Review, 1930)
Publisher: [American Geographical Society, Wiley]
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjonen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; lutfart; oppdagelsesreiser

Antarctic whaling and exploration - Aagaard, Bjarne (Scottish Geographical Magazine, 1929)
Publisher: Routledge
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Whaling and Exploring in the Antarctic - Aagaard, Bjarne (Norwegian Trade Review, 1929)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Amundsen: Supreme Adventurer - Finley, John H (Geographical Review, 1929)
Publisher: [American Geographical Society, Wiley]
Keywords: Antarktis; Roald Amundsen; ekspedisjoner; forskning; polarområdene

Litt om "Norveiga"-ekspedisjonen 1927-28 og dens arbeide - Holtedahl, Olaf (Norsk hvalfangst-tidende, 1929)
Keywords: Bouvetøya; Sørishavet; ekspedisjoner; forskning; geografi; marinbiologi; oseanografi

Modern Norwegian Whaling in the Antarctic - Isachsen, Gunnar (Geographical Review, 1929)
Publisher: [American Geographical Society, Wiley]
Keywords: Sørishavet; ekspedisjoner; forskning; historie; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk

Trekk av Sydishavets dyreliv - Olstad, Ola (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1928)
Publisher: Routledge
Keywords: Antarktis; Bouvetøya; Lars Christensen; Norvegia ekspedisjoner; Peter I. Øy; dyreliv; forskning; zoologi

The "Southern Cross" Expedition to the Antarctic, 1899-1900 - Borchgrevink, Carsten Egeberg (The Geographical Journal, 1900)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Southern Cross; biologi; ekspedisjonen; ekspedisjoner; forskning; geografi; meteorologi; oppdagelsesreiser; overvintring; zoologi

Den antarctiske expedition. Foredrag den 18de mai 1898 - Borchgrevink, Carsten Egeberg (Det Norske geografiske selskabs aarbok, 1898)
Publisher: Haffner & Hille Place: Kristiania
Keywords: Antarktis; Southern Cross (skip); forskning; oppdagelsesreiser; polarekspedisjoner; vitenskapelige ekspedisjoner

Antarctic exploration - Borchgrevink, Carsten Egeberg (Strand Magazine, 1897)
Keywords: Antarktis; Southern Cross; ekspedisjonen; ekspedisjoner; forskning; geografi; oppdagelsesreiser; overvintring

The First Landing On The Antarctic Continent : being An Account of the Recent Voyage Of The Whaler "Antarctic" - Borchgrevink, Carsten Egeberg (The Century illustrated monthly magazine, 1896)
Publisher: The Century Co. Place: New York
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

Den sidste antarctiske reise og foreløbig plan for en ny expedition. Foredrag den 30te oktober 1895 - Borchgrevink, Carsten Egeberg; Bull, Henrik Johan (Det Norske geografiske selskabs aarbok, 1896)
Publisher: Haffner & Hille Place: Kristiania
Keywords: Antarktis; Kapp Adare; forskning; første landgang; oppdagelsesreiser; overvintring; polarekspedisjoner

Is Antarctic exploration possible? (The Spectator, 1895)
Publisher: The Spectator
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Southern Cross; ekspedisjonen; ekspedisjoner; forskning; oppdagelsesreiser; overvintring

A Voyage to the Antarctic Sea - Borchgrevink, Carsten Egeberg (Report of the Sixty-Fifth meeting of the British Association for the Advancement of Science helt at Ipswich in September 1895, 1895)
Publisher: John Murray Place: London
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

The "Antarctic's" Voyage to the Antarctic - Borchgrevink, Carsten Egeberg (The Geographical Journal, 1895)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

The Voyage of the “Antarctic” to Victoria Land - Borchgrevink, Carsten Egeberg (Nature, 1895)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

Kapit. Larsens antarktische Entdeckungen - Petersen, J; Larsen, Carl Anton; Wichmann, Hugo (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1895)
Publisher: Perthes Place: Gotha
Keywords: Antarktis; Carl Anton Larsen; ekspedisjoner; forskning; geografi; geologi; hvalfangere; oppdagelsesreiser

Die Reisen des "Jason" und der "Hertha" in das Antarktische Meer 1893/94 : und die wissenschaftliche Ergebnisse dieser Reisen - Petersen, Johannes; Friedrichsen, Ludwig (Mitteilungen der Geographischen Gesellschaft in Hamburg, 1895)
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; Hertha (skip); Vestantarktis; dagbok; ekspedisjoner; forskning; geologi; hvalfangere; oppdagelsesreiser

Das Wiedererwachen der antarktischen Forschung - Wichmann, Hugo; [Hassenstein, Bruno] (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1895)
Publisher: Perthes Place: Gotha
Keywords: Antarktis; Carl Anton Larsen; D/S Antarctic; ekspedisjoner; forskning; geografi; geologi; hvalfangere; oppdagelsesreiser

Notes on an important geographical discovery in the Antarctic Regions - Murray, John (Scottish Geographical Magazine, 1894)
Publisher: Routledge
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; Vestantarktis; dagbok; ekspedisjoner; forskning; geografi; geologi; hvalfangere; oppdagelsesreiser

Das neu entdeckte Land im antarktischen Gebiet - Schück, Albert (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1894)
Publisher: Perthes Place: Gotha
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; dagbøker; ekspedisjoner; forskning; geografi; geologi; hvalfangere; oppdagelsesreiser